Maternal and Fetal Outcomes After Interferon Exposure During Pregnancy: A Systematic Review With Meta-Analysis - Zhang, Mengmeng; Fu, Shan; Ren, Danfeng; Wu, Yuchao; Yao, Naijuan; Ni, Tianzhi; Feng, YaLi; Chen, Yaolong; Chen, Tianyan; Zhao, Yingren; Liu, Jinfeng (Frontiers in Reproductive Health, 2021)
Interferon (IFN) treatment is widely applied in viral hepatitis and multiple myeloproliferative diseases. However, there is considerable controversy on how to deal with unintended pregnancy during IFN treatment, even selective termination is suggested by hepatologists. To settle this clinical dilemma, we conducted a systematic review to retrieve all published articles involving IFN exposure during pregnancy up until March 31, 2021. Only 8 case reports that were relevant with outcomes of pregnant women with viral hepatitis exposed to IFN-α were retrieved, and 17 studies reporting pregnancy outcomes after exposure to type I IFNs involving 3,543 pregnancies were eligible for meta-analysis. No birth defect was reported in the case reports of pregnant women with viral hepatitis. The meta-analysis showed that risks of pregnancy outcomes and birth defects were not increased after exposure to IFN-α. Further comprehensive meta-analysis concerning the IFN-α and IFN-β exposure demonstrated that the risks of live birth (OR 0.89, 95% CI: 0.62–1.27), spontaneous abortion (OR 1.09, 95% CI: 0.73–1.63), stillbirth (OR 1.38, 95% CI: 0.51–3.72), preterm delivery (OR 1.24, 95% CI: 0.85–1.81), and maternal complications (OR 0.72, 95% CI: 0.38–1.38) were not increased in patients exposed to IFNs. The pooled estimates of live birth, spontaneous abortion, stillbirth, preterm delivery, and maternal complications were 85.2, 9.4, 0, 7.5, and 6.5%, respectively. Importantly, the risk of birth defects was not increased (OR 0.68, 95% CI: 0.39–1.20) after IFN exposure, with a pooled rate of 0.51%. Therefore, IFN exposure does not increase the prevalence of spontaneous abortion, stillbirth, preterm delivery, and birth defects. Clinical decision should be made after weighing up all the evidence.